The suite of small‐angle neutron scattering instruments at Oak Ridge National Laboratory. Issue 2 (21st February 2018) - Heller, William T.; Cuneo, Matthew; Debeer-Schmitt, Lisa; Do, Changwoo; He, Lilin; Heroux, Luke; Littrell, Kenneth; Pingali, Sai Venkatesh; Qian, Shuo; Stanley, Christopher; Urban, Volker S.; Wu, Bin; et al.
Abstract : The suite of small‐angle neutron scattering instrumentation available at the High Flux Isotope Reactor and Spallation Neutron Source of Oak Ridge National Laboratory is presented. Abstract : Oak Ridge National Laboratory is home to the High Flux Isotope Reactor (HFIR), a high‐flux research reactor, and the Spallation Neutron Source (SNS), the world's most intense source of pulsed neutron beams. The unique co‐localization of these two sources provided an opportunity to develop a suite of complementary small‐angle neutron scattering instruments for studies of large‐scale structures: the GP‐SANS and Bio‐SANS instruments at the HFIR and the EQ‐SANS and TOF‐USANS instruments at the SNS. This article provides an overview of the capabilities of the suite of instruments, with specific emphasis on how they complement each other. A description of the plans for future developments including greater integration of the suite into a single point of entry for neutron scattering studies of large‐scale structures is also provided.